Drying kinetics and thermodynamic properties of peanut seeds (Arachis hypogaea L.) - MABASSO, Geraldo Acácio; RESENDE, Osvaldo; AMADE, Faruque Faruque; SIQUEIRA, Valdiney Cambuy; SOUZA, Diene Gonçalves (Food Science and Technology, 2025)
The aim of this study was to evaluate the drying process and determine the activation energy, effective diffusion coefficient, and thermodynamic properties of peanut seeds. The peanut seeds (variety “Amena 018”), harvested with an initial moisture content of 0.36 ± 0.003 kg kg-1 db, were dried in a forced circulation oven at temperatures of 40, 45, 50, 55, and 60°C until they reached a final moisture content of 0.11 ± 0.001 kg kg-1 db. The mathematical models were adjusted by nonlinear regression using the Gauss-Newton method, Akaike’s information criterion (AIC), and Schwarz’s Bayesian information criterion (BIC). The two-term model showed the best fit for the temperatures of 40, 45, 50, and 55°C, and the two-term exponential for 60°C; the drying rate increased with increasing temperature and decreased with increasing drying time, the effective diffusion coefficient varied from 7.5097 × 10-11 to 11.5741 × 10-11 m2 s-1 for the 40-60°C range, and the activation energy was 18.54 kJ mol-1. The enthalpy, entropy, and Gibbs free energy values ranged from 15.931 to 15.765 kJ mol-1, -0.110401 to -0.110916 kJ mol-1 K-1, and 50.504-52.718 kJ mol-1, respectively, for temperatures from 40 to 60°C.